Adapting terminology: clarifying prism adaptation vocabulary, concepts, and methods. (April 2020) - Prablanc, C.; Panico, F.; Fleury, L.; Pisella, L.; Nijboer, T.; Kitazawa, S.; Rossetti, Y.
Highlights: Adaptation terminology is commonly confused about concepts and methodology. We provide clear definition of concepts for the design of future adaptation studies. Recommendations are made for appropriate prism adaptation terminology. A distinction is drawn between true adaptation and sensori-motor learning processes. Abstract: When individuals are exposed to a constant change of the interplay with their environment, they are able to develop compensatory alterations of visuo-motor coordination in order to counteract the perturbation. Prism adaptation (PA) is a very simple tool that has been used for several decades to investigate adaptive processes. However, the specific terminology used in PA literature has continuously evolved and is still subjected to broad inconsistency. Growing confusion about the choice of terms used to describe specific processes and methods has yielded the critical need for clarifying the adaptation vocabulary. The aim of this terminology review is to consider and to describe the most common terms used in PA literature in order to ensure more consistent communication in future research. On the basis of a descriptive examination of previous studies on PA, we provide specification for each term, indicating whether it refers to a classical term in PA literature, and whether it is recommended or should be used with particular attention. This glossary represents a useful instrument to both new readers and experts in the field of PA in order to facilitate unambiguous communication and consensual comparisons between individual investigations. Recommendations for the use of consistent paradigms and reliable vocabulary are provided for future investigations, in both basic and clinical research.